Development of a New Shoe Fitting for Obese Adults (Bangladesh Journal of Medical Science, 2022)
Background: Standard fit as well as wide-fit footwear not currently being pertinent and comfortable for the obese adults. The biometric measurements of obese foot (such as foot length, foot width, heel girth, instep girth, waist girth, and ball girth,) significantly differ from healthy adults.Aim: This study aims to develop a new shoe fitting for obese adults based on significant relationships among the relevant biometric parameters of the foot.Method: These measurements of obese foot were determined using a Brannock device and measuring tape. All kinds of foot girth measurements were analyzed against scaling based on foot width or current fitting, BMI, foot length, heel girth, instep girth, waist girth and ball girth and compared these data with ANOVA.Result: Results showed that responses of all kinds of girths against waist girth scaling provide best fitting prospects of obese adults than current standard fit as well as other parameters.Conclusion: From the study and results, it can be concluded that shoe fitting based on waist girth can give more precise comfort and improve the ergonomic fitness of the product for obese users.Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 45-53